Gene x Gene Interactions Highlight the Role of Incretin Resistance for Insulin Secretion - Jaghutriz, Benjamin Assad; Heni, Martin; Lutz, Stefan Zoltán; Fritsche, Louise; Machicao, Fausto; Staiger, Harald; Peter, Andreas; Häring, Hans-Ulrich; Fritsche, Andreas; Wagner, Róbert (Frontiers in Endocrinology, 2019)
Introduction: Genetic polymorphisms in TCF7L2 are the strongest common risk variants for type 2 diabetes mellitus (T2D). We and others have shown that genetic variation in TCF7L2 and WFS1 affect incretin-stimulated insulin secretion. A recent genome-wide association study discovered genetic variants associated with incretin levels. We hypothesized that these SNPs (single nucleotide polymorphisms) interact with the well-known TCF7L2 variant rs7903146 on insulin secretion due to their incretin altering effect. Methods: In this retrospective analysis, we used data from the cross-sectional TUEF-cohort (n=2929) and a hyperglycemic clamp study using additional GLP-1 infusion at the end of the clamp (n=76). Insulin secretion was measured by evaluating OGTT-derived indexes of insulin secretion and insulin/C-peptide levels during clamp. We genotyped rs7903146 in TCF7L2, rs10010131 in WFS1, and six SNPs associated with GLP-1 and GIP levels. Results: One of the six incretin-associated SNPs, rs17681684 in GLP2R, exhibited significant SNP x SNP interactions with rs7903146 in TCF7L2 on insulin secretion (p=0.0024) after correction for multiple testing. Three further SNP`s showed nominally significant interactions (p<0.05). In the hyperglycemic clamp study, rs7903146 in TCF7L2 also interacted with rs17681684 on AUC C-peptide during the GLP-1 stimulation phase, thereby replicating the above finding. Conclusion: The findings exemplify the role of SNP x SNP interactions in the genetics of type 2 diabetes mellitus and corroborate the existence of clinically relevant differences in incretin sensitivity.